Research progress on arsenic, arsenic-containing medicinal materials, and arsenic-containing preparations: clinical application, pharmacological effects, and toxicity - Yang, Yichu; Li, Yiye; Li, Ran; Wang, Zhang (Frontiers in Pharmacology, 2024)
The toxicity of arsenic is widely recognized globally, mainly harming human health by polluting water, soil, and food. However, its formulations can also be used for clinical treatment of diseases such as leukemia and tumors. Arsenic has been used as a drug in China for over 2400 years, such as the arsenic containing drug realgar in the Shennong's Herbal Classic. The finding showed that in clinical practice, arsenic trioxide is mainly used in combination with ATRA at a dose of 10mg/d for the treatment of acute promyelocytic leukemia; Realgar can be used to treat acute promyelocytic leukemia, myelodysplastic syndrome, and lymphoma. In terms of pharmacology, arsenic mainly exerts anti-tumor effects. The dosage range of action is 0.01 to 80 µmol/L, and the concentration of arsenic in most studies does not exceed 20 µmol/L. The pharmacological effects of Realgar include antiviral activity, inhibition of overactivated lactate dehydrogenase, and resistance to malaria parasites. In terms of toxicity, arsenic is toxic to multiple systems in a dose-dependent manner. For example, 5 µmol/L sodium arsenite can induce liver oxidative damage and promote the expression of pro-inflammatory factors, and 15µmol/L sodium arsenite induces myocardial injury; When the concentration is higher, it is more likely to cause toxic damage. This article reviews the clinical application, pharmacological effects, and toxicity of arsenic, in order to avoid its toxicity, enhance its therapeutic effect, and provide a theoretical basis for clinical medication and the development of arsenic agents.